PENGEMBANGAN MEDIA BERBASIS HOLOGRAM DALAM PEMBELAJARAN TEMATIK TEMA 8 SUBTEMA 1 DI KELAS V SEKOLAH DASAR NEGERI 18 SUNGAI KAKAP - Rahmawati, Dwi Ayu; Sugiyono, Sugiyono; Kartono, Kartono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
Abstract This study aims to develop a suitable holographic-based learning media for thematic learning in elementary schools. The approach used in this study is the research & development (R&D) proposed by Borg and Gall. Of the ten steps of the study, only nine steps were taken for this research was limited to testing the product's feasibility. Sources of data in this study came from teachers, media experts, material experts, and students. Data collection techniques used were observation, interviews, and questionnaires. The research instruments used were the interview and questionnaire guidelines. The product validation by media experts occurred in two stages, obtaining an average score of 3.57 with excellent criteria. Validation by material experts passed in three stages, acquiring an average score of 4.00 with excellent criteria. The field trials were occurred in three stages, with the results of operational field trials with an average score of 3.46 with very good criteria. Based on these criteria, the holographic-based learning media product is feasible as a thematic learning media theme 8 subthemes 1 in class V SD Negeri 18 Sungai Kakap. Keywords: Development, Holographic-Based Learning Media, Thematic Learning